Effect of UV-B Radiation on Flavonoids and Phenols Accumulation in Tempisque (Sideroxylon capiri Pittier) Callus - Karina E. Martínez-Silvestre; José Alfredo Santiz-Gómez; María Celina Luján-Hidalgo; Nancy Ruiz-Lau; Yazmin Sánchez-Roque; Federico A. Gutiérrez-Miceli (Plants, 2022)
Tempisque (Sideroxylon capiri Pittier) is classified as a threatened species and has been reported with a high content of phenols and flavonoids in the leaves. The use of abiotic elicitors such as radiation has been reported due to the changes it produces in the metabolism of plants by activating their defense mechanisms and increasing the biosynthesis of bioactive compounds with antioxidant capacity such as phenols and flavonoids. Therefore, the aim of this work was to evaluate the effect of UV-B radiation on growth parameters and the synthesis of bioactive compounds in in vitro culture of tempisque callus. For the callus induction, we used thidiazuron (TDZ) and 2,4-dichlorophenoxyacetic acid (2,4-D) at 0, 0.5 and 1 mg/L. Calluses were exposed to UV-B radiation (0, 1, 2, 3 and 4 h/day) for two and four weeks. The highest callus formation index was obtained with TDZ and 2,4-D at 1 mg/mL. The greatest increase in the concentration of phenols and flavonoids was detected in the fourth week with 4 h of exposure per day. The highest concentrations of quercetin (230 µg/g dry weight), kaempferol (235 µg/g dry weight) and gallic acid (240 µg/g dry weight) were found in callus obtained from leaves explants.